2013
DOI: 10.1210/jc.2012-3838
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation of the Subthalamic Nucleus Regulates Postabsorptive Glucose Metabolism in Patients With Parkinson's Disease

Abstract: Deep brain stimulation in patients with PD affects EGP glucose disposal, suggesting that a cross talk between the central nervous system and peripheral tissues may regulate glucose homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
1
13
1
Order By: Relevance
“…Our results seem in contrast with an earlier report on lower EGP upon STN DBS, i.e., Batisse-Lignier et al showed that basal EGP was decreased in the stimulated condition (Batisse-Lignier et al, 2013). However, the 22% decrease in EGP in that study could alternatively be explained by the physiological adaptation to fasting since EGP was measured in both the non-stimulated and stimulated condition, consecutively on one study day, and thus with a difference in hours of fasting.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results seem in contrast with an earlier report on lower EGP upon STN DBS, i.e., Batisse-Lignier et al showed that basal EGP was decreased in the stimulated condition (Batisse-Lignier et al, 2013). However, the 22% decrease in EGP in that study could alternatively be explained by the physiological adaptation to fasting since EGP was measured in both the non-stimulated and stimulated condition, consecutively on one study day, and thus with a difference in hours of fasting.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies on glucose metabolism in patients with PD and DBS are scarce. One study showed a reduction in endogenous glucose production (EGP) with STN DBS (Batisse-Lignier et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Some subsequent studies showed an acute rise in blood glucose levels 20 minutes after electroconvulsive therapy application in diabetic and non‐diabetic patients . Furthermore, Batisse‐Lignier et al observed a decrease in endogenous glucose production upon deep brain stimulation in Parkinson's disease, confirming the assumption of communication between the central nervous system and peripheral tissues, which may regulate systemic glucose homeostasis. The results of these studies suggest that direct current‐induced modulation of brain functioning not only affects the brain itself, but also exerts a significant further influence on a number of peripheral functions.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, motor improvement actually may help protect against WG in STN‐stimulated patients, because the increase in physical activity made possible by newly acquired motor abilities counterbalances the reduction in energy expenditure arising from the alleviation of motor symptoms . Alternatively, DBS has been hypothesized to affect the central regulation of eating behavior or energy metabolism . Decreased energy expenditure has thus been attributed either to motor improvements or to action on the centers that control metabolism …”
mentioning
confidence: 99%